آليات تأويل الخطاب الشعري بين إشكالات تعدد المصطلح وتحديات تلقيّه - زايدي لمين (Université de M'sila, 2019)
تناولت هذا الورقة قضيتين مهمتين وهما؛ آليات تفسير الخطاب الشعري،و إشكالية المصطلح النقدي في الدرس النقدي،حيث تتنوع مناهج تحليل الخطاب الشعري مابين المنهج التداولي والبنيوي والأسلوبي والتفكيكي،و السميائي ورغم اختلاف المنهجيات هذه المناهج إلا إنها تسعى كلها إلى تجزئة الخطاب الشعري وتبسيطه لمتلقي، و يعاني الدرس النقدي العربي من معضلات من بينها مشكلة تعدد المصطلحات النقدية على الساحة النقدية العربية،ويعود سبب هذا التعدد المصطلحي النقدي إلي التفرد في وضع المصطلحات النقدية، كما تحاول الجامع العربية إقامة الندوات والمؤتمرات ،وهذا لخلق الحوار بين الباحثين والنقاد ،و هذا لإيجاد الحلول المناسبة لتوحيد المصلحات النقدية وحتى اللسانية This paper dealt with two important issues: mechanisms of interpretation of poetic discourse, and the problematic of the critical term in the critical lesson, where the methods of analysis of poetic discourse vary between the deliberative, structural, stylistic, deconstructive, and semiotical, and despite the different methodologies these approaches, but they all seek to fragment the poetic discourse and simplify it to the recipients The Arab critical lesson suffers from dilemmas, including the problem of multiple monetary terms on the Arab monetary scene. The reason for this monetary term is due to the uniqueness in the development of monetary terminology. This is to create a dialogue between researchers and critics, and to find appropriate solutions to unify critical and even linguistic reforms.
Keywords: الخطاب الشعري،المصطلح النقدي،الأسلوبية،البنيوية،التداولية